ANALISIS PERILAKU KONSUMEN DALAM KEPUTUSAN PEMBELIAN MAKANAN DI KOTA SURAKARTA - Muzakar Isa; Robingatun Istikomah (Jurnal Manajemen Dayasaing, 2019)
Every SME actor must strive to influence consumer decisions in choosing products and services to meet their needs and desires. This study aims to analyze the effect of prices on purchasing decisions, analyze the influence of product quality on purchasing decisions, analyze the influence of service quality on purchasing decisions, and analyzes the effect of word of mouth on purchasing decisions. The study was conducted in the Surakarta city of Galabo culinary tourism area. The population of this study is consumers who visit and enjoy culinary at Galabo. The research sample was 100 people, and the sampling used a purposive sampling method. The data used is primary data. Data collection used questionnaire and interview. The analytical tool used is multiple linear regression analysis. The results showed that the price and Word of mouth had a positive and significant influence on purchasing decisions on Galabo Surakarta City Culinary, while the quality of products and services had a positive but not significant effect on purchasing decisions on Galabo Surakarta City Culinary.